A Study on the Effect of Nursing Intervention Based on Health Behavior Change Integration Theory on Patients with Limb Fracture and Its Effect on Limb Function and Self-Efficacy. (13th July 2022) - Luo, Shunhong; Xie, Yu; He, Shangwen; Li, Jian; He, Chunhua
Abstract : Objective . To assess the impact on nursing care based on the theory of health behavior change integration in patients with limb fracture and its effect on limb function and self-efficacy. Methods . The starting and ending time of this study is from February 2021 to February 2022. In this study, 116 hospitalized patients with limb fracture were selected as the object of study. According to the method of random number table, the patients were divided into study group and control group. The patients of the study cohort were given nursing healthcare based on the theory of health behavior change integration, while those in the control cohort were given common nursing. The scores of self-rating anxiety scale (SAS), self-rating depression scale (SDS), Frankl compliance scale, self-efficacy scale (GSES), activity of daily living scale (ADL), and Fugl-Meyer limb motor function assessment (FMA) were studied before and 3 months after nursing. Results . After 3 months of nursing, the SAS and SDS scores of the study group were lower than those of the control group, and the difference between groups was statistically significant (p < 0.05 ). After 3 months of nursing, the scores of Frankl scale, GSES, ADL scale, and FMA scale in the study group were higher than those in the control group, and the difference between groups was statistically significant (p < 0.05 ). Conclusion . The value of nursing interventions based on the integration of health behavior change theory is even more significant in patients with limb fractures. It is more helpful in reducing patients' anxiety and depression, increasing compliance and improving limb function. Self-efficacy and daily living skills were also significantly improved.